Leaders’ and followers’ individual experiences during the early phase of simulation-based team training: an exploratory study - Meurling, Lisbet (BMJ Publishing Group, 2013)
BACKGROUND: A growing body of evidence shows that team training can develop essential team skills and contribute to better patient outcomes. Current simulation-based team training (SBTT) programmes most often include targets and feedback focused on the whole team and/or leader, ignoring the follower as a unique entity. By considering followers’ individual experiences, and tailoring behavioural targets for training and feedback, SBTT could be improved. Our aim was to explore the individual experiences and behaviours of leaders and followers during the early phase of SBTT, and we hypothesised that leaders and followers would show different responses. METHODS: Medical students (n=54) participated in half-day SBTT including three video-recorded scenarios. Self-efficacy was assessed pretraining and post-training. For each scenario (n=36), the individual teamwork behaviours, concentration, mental strain and the team's clinical performance were recorded. Data were analysed using a mixed model allowing for participants to be their own control in their roles as leader or follower. RESULTS: Self-efficacy improved. In the role of leader, participants communicated to a greater extent and experienced higher mental strain and concentration than they did in the role of follower. DISCUSSION: The increased self-efficacy enables a positive learning outcome after only three scenarios. Individual experiences and behaviours differed between the role of leader and that of follower. By shedding further light on leaders’ and followers’ individual experiences and behaviours, targets for training and feedback could be specified in order to improve SBTT.